The effects of green space and physical activity on muscle strength: a national cross-sectional survey with 128,759 Chinese adults - Feng, Qiang; Fan, Chao-Qun; Wang, Jing-Jing; Wang, Huan; Wu, Dong-Ming; Nassis, George P.; Wang, Mei; Wang, Hai-Jun (Frontiers in Public Health, 2023)
Objective: This study explored whether green spaces are associated with muscle strength and ascertained the combined effect of physical activity and green spaces on muscle strength. Method: Data from 128,759 participants (age 20–79 years) were obtained using a complex stratified multistage probability cluster sampling design. The green space is assessed as normalised difference vegetation index (NDVI) data for a 500-m buffer according to the geographical location information of sampling sites. We used a questionnaire to investigate transportation, occupation, physical activity, leisure-time exercise behaviours, and sedentary time within the usual last week in the preceding year. The outcome was low relative handgrip strength (HS; handgrip strength and body weight ratio) and the percentage of people with relative HS in the lower third among male and female. We defined adequate physical activity as 150 min of moderate-intensity or 75 min of vigorous physical activity per week and calculated the weighted rate of participants who had adequate physical activity. Categorical variables of NDVI and physical activity were used as exposure variables and their interrelationship was evaluated in a general linear mixed model (GLMM) to estimate the odds ratios and 95% confidence intervals (95% CI). We measured interaction on an additive or multiplicative scale using a GLMM to test the interaction between green space and physical activity. All analyses were conducted for the total sample and subgroups (urban and rural ). Result: Compared with the low NDVI group, the high NDVI group had a decreased risk of low relative HS (OR [95% CI]: 0.92 [0.88–0.95]). Compared to the insufficient physical activity group, the adequate physical activity group had a decreased risk of low relative HS (0.85 [0.81–0.88]). There was an interaction effect on the additive scale (relative excess risk due to interaction, RERI: 0.29, 95% CI 0.22–0.36, p<0.001) between green space and physical activity. Conclusion: High NDVI exposure and adequate physical activity were low relative HS protection factors in Chinese adults. Increasing green space and physical activity together may improve muscle strength levels with a potentiating effect than these two risk factors alone. Green spaces should be incorporated in city design or built environments.